Examining the adoption of blended learning among Malaysian Academicians - Nurjeehan Ayub; Md. Hafizi Ahsan @ Miskam; Cheah, Yeh Ying (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2019)
To date, there are a growing number of higher learning institutions in Malaysia begin to adopt blended learning as a new teaching method in tandem with Malaysia Education Blueprint 2025. For centuries, a traditional method of teaching is now described as a passive teaching mode because they discourage students from critically filtering the delivered information. For this purpose, the present study intends to examine the effects academicians’ interest, ICT facilities, perceived ease of use and adequate training on the system adoption. Evidently, the result shows that academician interest, adequate training and perceived ease of use are the main important determinant in adopting the blended learning approach among Malaysian academicians. This study contributes to present literature on blended learning effectiveness particularly in Malaysian context. The outcomes obtained can benefit all lecturers, students as well as management of the university and indirectly enhanced the quality of the university itself.